Compulsive water drinking in adolescents: Report of two cases - Sethi, Sujata; Bhargava, Subhash C. (Journal of Pediatric Neurology, 2006)
Compulsive water drinking has been described as a symptom in various psychiatric disorders but not as an independent entity. We describe two cases in which compulsive water drinking was the only presenting complaint. The case is discussed further in regards to its nosological status and its response to selective serotonin re-uptake inhibitors.
Keywords: Compulsive water drinking; obsessive-compulsive disorder; selective serotonin re-uptake inhibitors